1997
DOI: 10.1084/jem.185.7.1371
|View full text |Cite
|
Sign up to set email alerts
|

RANTES and Monocyte Chemoattractant Protein–1 (MCP-1) Play an Important Role in the Inflammatory Phase of Crescentic Nephritis, but Only MCP-1 Is Involved in Crescent Formation and Interstitial Fibrosis

Abstract: The involvement of chemokines in inflammation is well established, but their functional role in disease progression, and particularly in the development of fibrosis, is not yet understood. To investigate the functional role that the chemokines monocyte chemoattractant protein–1 (MCP-1) and RANTES play in inflammation and the progression to fibrosis during crescentic nephritis we have developed and characterized a murine model for this syndrome. Significant increases in T-lymphocytes and macrophages were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
344
1
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 469 publications
(358 citation statements)
references
References 32 publications
12
344
1
1
Order By: Relevance
“…MCP-1 has previously been reported to be a major profibrotic chemokine involved in various fibrotic processes, including recruitment of fibrocytes, induction of collagen synthesis, and up-regulation of TGF-␤1 expression in various models. 50,51,[55][56][57][58][59][60][61][63][64][65][66][67][68] Indeed, we observed that MCP-1 responses preceded the responses of fibrogenic growth factor TGF-␤1, 51,52 which were significantly higher in the lung of infected TNF Ϫ/Ϫ lungs and were well correlated with fibrotic tissue remodeling seen in TNF Ϫ/Ϫ lungs at later time points during influenza infection. Thus, depletion of MCP-1 in influenza-infected TNF Ϫ/Ϫ hosts markedly reduced lung immunopathology and tissue remodeling, and such MCP-1 depletion-improved welfare was associated with diminished production of bioactive TGF-␤1.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…MCP-1 has previously been reported to be a major profibrotic chemokine involved in various fibrotic processes, including recruitment of fibrocytes, induction of collagen synthesis, and up-regulation of TGF-␤1 expression in various models. 50,51,[55][56][57][58][59][60][61][63][64][65][66][67][68] Indeed, we observed that MCP-1 responses preceded the responses of fibrogenic growth factor TGF-␤1, 51,52 which were significantly higher in the lung of infected TNF Ϫ/Ϫ lungs and were well correlated with fibrotic tissue remodeling seen in TNF Ϫ/Ϫ lungs at later time points during influenza infection. Thus, depletion of MCP-1 in influenza-infected TNF Ϫ/Ϫ hosts markedly reduced lung immunopathology and tissue remodeling, and such MCP-1 depletion-improved welfare was associated with diminished production of bioactive TGF-␤1.…”
Section: Discussionmentioning
confidence: 83%
“…51,[62][63][64][65][66][67][68] Thus, given the dysregulated MCP-1 and its association with heightened TGF-␤1 production seen in influenza-infected TNF Ϫ/Ϫ lungs (Figure 7), we further investigated the role of MCP-1 in heightened immunopathology and fibrotic reaction in the lung of TNF Ϫ/Ϫ mice by means of MCP-1 depletion. To this end, MCP-1 anti-serum (anti-MCP-1) or the control serum was administered intraperitoneally to TNF Ϫ/Ϫ mice on days 2, 5, and 9 following influenza infection, and the mice were sacrificed at day 21 after infection for morphometric quantification of lung immunopathology and fibrotic remodeling ( Figure 8A).…”
Section: Attenuation Of Lung Immunopathology In Influenza-infected Tnmentioning
confidence: 99%
“…Both CCL5/RANTES analogs have been shown to block CCL5/ RANTES binding to its respective human chemokine receptor CCR5 and to the murine CCR5 and to block leukocyte chemotaxis in vitro (20). Treatment with Met-RANTES decreased leukocyte infiltration in rat renal transplant rejection and in murine NSN (10,21,22). AOP-RANTES reduced the early influx of monocytes into the glomerulus after injection of the anti-Thy1.1 Ab in rats (23).…”
Section: P Roliferative Immune Complex Glomerulonephritis (Gn)mentioning
confidence: 99%
“…Chemokine blockade with specific Abs or chemokine antagonists has been shown to reduce monocyte influx and proteinuria in some of these models (7,10,11). Therefore, chemokine antagonism is thought to be a promising therapeutic approach for proliferative GN as well as for many other inflammatory diseases (12)(13)(14)(15)(16).…”
Section: P Roliferative Immune Complex Glomerulonephritis (Gn)mentioning
confidence: 99%
“…Studies with Fc receptor (FcR) ␥-chain-deficient mice have shown that macrophage activation by immune complex through the FcR is essential for amplification of glomerular inflammation. Activated macrophages could be the prime source of inflammatory monokines such as tumor necrosis factor ␣ (TNF␣) and interleukin-1␤ and chemokines such as monocyte chemotactic protein 1 (14). Disease peaks on day 14, at which time proteinuria ensues.…”
Section: Urine Proteomics and Excreted Urinary Mediators In Experimenmentioning
confidence: 99%